2008
DOI: 10.1007/s10765-008-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Porosity Effects on the Thermal Radiative Behavior of Alumina Ceramics

Abstract: International audienceThermal and optical properties of ceramics are dependent on radiation scattering and cannot be determined by a knowledge of their chemical composition alone, as for single crystals. In this paper, extrinsic effects, such as roughness, porosity, and texture, on the spectral emissivity of alumina ceramics are investigated. Roughness effects have an influence mainly in the opaque zone; an important porosity dependence and the presence of a critical porosity threshold were observed in the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…The photodiode signal increases more progressively that with pure methane air flames but the amplitude are higher (double). All of this would also suggest that the emissivity of alumina is not zero but rather low in agreement with recent data (Rozenbaum and al., 2009) With SiC particle (figure 11), the radiated flux is much higher than with the pure gaseous mixture when the dust concentration is 500 g/m 3 but smaller for a higher concentration (800 g/m 3 ). These dust concentrations might be too large since a proportion of the dust can fall down in the maps of time between the interruption of the flow and the ignition.…”
Section: Fig 8 Signals Delivered By the Transducers (10% V/v Ch 4 -supporting
confidence: 92%
“…The photodiode signal increases more progressively that with pure methane air flames but the amplitude are higher (double). All of this would also suggest that the emissivity of alumina is not zero but rather low in agreement with recent data (Rozenbaum and al., 2009) With SiC particle (figure 11), the radiated flux is much higher than with the pure gaseous mixture when the dust concentration is 500 g/m 3 but smaller for a higher concentration (800 g/m 3 ). These dust concentrations might be too large since a proportion of the dust can fall down in the maps of time between the interruption of the flow and the ignition.…”
Section: Fig 8 Signals Delivered By the Transducers (10% V/v Ch 4 -supporting
confidence: 92%
“…2. It was reported that the porosity had the positive effect on the emissivity in Si, SiO 2 and Al 2 O 3 materials [3,4,17]. The pores in the CeO 2 coating are similar to blackbody cavities.…”
Section: Resultsmentioning
confidence: 99%
“…Sample was heating by the back face with metallic heater. This configuration is known to be not well adapted for sample with poor thermal conductivity such ceramics [14,16]. In this case the surface temperature may be lower than expected and we have a wrong calculation of luminance of the sample (eq 6) which gives a lower emittance.…”
Section: Uv Vis Nir Measurement Of Hemispherical Reflectance In Tempementioning
confidence: 95%
“…This choice is justified since SiC is one of the materials used for high temperature receiver (tower technology) [13]. The -Al2O3 is largely used for the emittance measurement in the range of high temperature [14,15,16] and can be considered as a reference materials. …”
Section: -4mentioning
confidence: 99%